Financial attitude and financial behavior analysis towards student financial literacy in Kupang City - Maria Bernadethe Mawarni Gelu Wutun; Simon Sia Niha; Henny A. Manafe (Enrichment : Journal of Management, 2023)
A child from an early age should have been taught and accustomed to saving money by his parents at home. This will help his future, especially when he grows up, he becomes good at managing finances for needs, savings and wants. A student's knowledge of finance is very important because it will help him manage the money he has as well as possible for daily needs without any difficulties at certain times. This study will analyze the influence of two independent variables, namely financial attitude and financial behavior, on the level of financial literacy of students in Kupang City. The study involved a sample of 100 students from Kupang City who filled out a Google form, which was then used to collect data. Responses to incoming questionnaires will be processed using a statistical program, namely SPSS.26. Analysis of the study data revealed that, while financial behavior did not significantly affect students' financial literacy, financial attitudes had a considerable impact. The results of the concurrent assessment show a strong correlation between students' attitudes and financial behavior, which ultimately has a significant impact on the overall level of students' financial literacy in Kupang City. This result certainly means that students really need to be equipped with knowledge about financial literacy which is very useful for the future in front of them. Good financial knowledge will determine good financial decisions as well.